A qualitative exploration of recognition and judgement in social work practice with street children in Ghana. - Teye, Abraham Tetteh (Journal of Social Work Practice, 2026)
This study explored how social work practitioners in Ghana conceptualise and implement the principles of recognition and judgement when working with street children in Accra. The study used a qualitative research design based on semi-structured interviews with 15 social work practitioners who had direct field experience with street children. The findings of the study revealed that social work practitioners implemented interventions that addressed the needs of street children while also being culturally sensitive. However, social work practitioners also faced challenges related to the cultural norms and beliefs that shaped the experiences of street children. Social work practitioners had to challenge negative stereotypes about street children, recognise their fundamental rights, and empower them to take control of their lives. This suggests that recognition and judgement are fundamental components in social work interventions for street children, as they can improve the effectiveness of interventions.